2018
DOI: 10.1093/nar/gky815
|View full text |Cite
|
Sign up to set email alerts
|

Mb- and FnCpf1 nucleases are active in mammalian cells: activities and PAM preferences of four wild-type Cpf1 nucleases and of their altered PAM specificity variants

Abstract: Cpf1s, the RNA-guided nucleases of the class II clustered regularly interspaced short palindromic repeats system require a short motive called protospacer adjacent motif (PAM) to be present next to the targeted sequence for their activity. The TTTV PAM sequence of As- and LbCpf1 nucleases is relatively rare in the genome of higher eukaryotic organisms. Here, we show that two other Cpf1 nucleases, Fn- and MbCpf1, which have been reported to utilize a shorter, more frequently occurring PAM sequence (TTN) when te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 54 publications
(77 reference statements)
5
46
0
Order By: Relevance
“…Our results agree with recent work [45] which demonstrated that FnCas12a does exhibit activity in mammalian cells, but only when used with a TTTV PAM site. It is important to note that while Zetsche et al [3] showed that a TTV PAM site appears to be sufficient to induce FnCas12a cleavage, it appears to be the least efficient motif that permits DNA binding (which could explain why FnCas12a was found to be ineffectual for mammalian cell editing using a TTV PAM site).…”
Section: Fncas12a Binding Energies Depend On An Extended Pam Sequencesupporting
confidence: 93%
“…Our results agree with recent work [45] which demonstrated that FnCas12a does exhibit activity in mammalian cells, but only when used with a TTTV PAM site. It is important to note that while Zetsche et al [3] showed that a TTV PAM site appears to be sufficient to induce FnCas12a cleavage, it appears to be the least efficient motif that permits DNA binding (which could explain why FnCas12a was found to be ineffectual for mammalian cell editing using a TTV PAM site).…”
Section: Fncas12a Binding Energies Depend On An Extended Pam Sequencesupporting
confidence: 93%
“…7c). Considering these and additional enCas12a variants (Gao et al, 2017;Kim et al, 2016;Tóth et al, 2018;Kleinstiver et al, 2019;Sanson et al, 2019) renders approx. 97% of all human genes accessible for C-terminal PCR tagging (Fig.…”
Section: Crrna Design Pam Site Selection and Genomic Coveragementioning
confidence: 99%
“…The protospacer sequence should preferably not contain four or more 'T'-s in a row, since this might lead to premature termination of the Pol III transcription of the crRNA (Arimbasseri et al, 2013) In practice, we observed that crRNAs with 'TTTT' are frequently functional. PAM sites are ranked according to literature (Gao et al, 2017;Kim et al, 2016;Tóth et al, 2018;Kleinstiver et al, 2019;Sanson et al, 2019). In addition, unconventional PAM sites were considered (MCCC for the AsCas12a RR variant and RATR for LbCas12a RVR variant), based on depositor comments on the Addgene webpage.…”
Section: Sequencementioning
confidence: 99%
“…For instance, the originally employed Streptococcus pyogenes Cas9 (SpCas9) restricted the choice of target sequence by sequence requirement of a DSB-proximal NGG protospacer adjacent motif (PAM) trinucleotide. However, this could be overcome by turning to naturally occurring CRISPR-associated enzymes from other species or by reengineering or evolving Cas9 to achieve alternative or relaxed RGN specificities [45–49]. Of note here are Staphylococcus aureus Cas9, which is particularly small and therefore most suited for adeno-associated virus (AAV)-mediated delivery [50, 51], and the Cas12a (aka Cpf1, C RISPR from P revotella and F rancisella ) RGN system.…”
Section: Crispr/cas Versatilitymentioning
confidence: 99%